2014
DOI: 10.1136/bmjopen-2013-004640
|View full text |Cite
|
Sign up to set email alerts
|

‘Shouting from the roof tops’: a qualitative study of how children with leukaemia are diagnosed in primary care

Abstract: ObjectivesTo investigate the prehospital presentation of paediatric leukaemia and identify the disease and non-disease related factors which facilitate or impede diagnosis.DesignThematic analysis of qualitative semistructured interviews.SettingOne tertiary referral centre in Southern England.Participants21 parents and 9 general practitioners (GPs) of 18 children (<18-year-old) with a new diagnosis of acute leukaemia.ResultsThe majority of children were first seen by GPs before the characteristic signs and symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 14 publications
(14 reference statements)
2
68
0
Order By: Relevance
“…Over half of the citations were classed as expert opinion including 20 educational articles 5,6,8,9,14,15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] and five editorials or commentaries. 13,[33][34][35][36] Twelve citations were studies using qualitative methods including five interview methods, [37][38][39][40][41] two questionnaire methods, 7,42 and five mixedmethod studies. [43][44][45][46][47] Of the remaining…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of the citations were classed as expert opinion including 20 educational articles 5,6,8,9,14,15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] and five editorials or commentaries. 13,[33][34][35][36] Twelve citations were studies using qualitative methods including five interview methods, [37][38][39][40][41] two questionnaire methods, 7,42 and five mixedmethod studies. [43][44][45][46][47] Of the remaining…”
Section: Resultsmentioning
confidence: 99%
“…Of the included citations, 24 provided advice on when safety netting should be used. 5,7,8,13,16,20,[24][25][26][30][31][32][33][36][37][38]40,42,44,45,49,52,54,55 It was recommended when there is diagnostic uncertainty and the differential diagnosis includes serious illness or illness that may progress rapidly. The MDU states that 'safety netting is important where a patient may have risk factors for a specific disease or where specific complications are recognised as part of the illness'.…”
Section: Timing and Recipients Of Safety Nettingmentioning
confidence: 99%
“… 31–34 A study from the UK reported that the GP–parent relationship had significant impact on the process of obtaining a paediatric leukaemia diagnosis. 34 For example, the GP’s concerns and actions were partly shaped by how anxious she/he estimated the parents to be. The GP’s initial perception of a parent as being a ‘worrier’ or too sensitive could influence the way the parents’ concerns are dealt with; ‘worriers’ are generally taken less seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing delay in diagnosis is also the focus of public health awareness campaigns 7. Recent published literature has focused on primary care and tertiary care populations and how cancer diagnoses are reached in those settings 3 8…”
Section: Introductionmentioning
confidence: 99%